Integrating Local Wisdom with Project-Based Learning to Enhance 21st-Century Skills in the Society 5.0 Era - Zaki, Ahmad; Mulbar, Usman; Husniati, Andi; Naufal, Muhammad Ammar (Journal of Ecohumanism, 2024)
In the context of Society 5.0, education must equip students with essential 21st-century skills such as problem-solving, collaboration, and creativity. However, traditional teacher-centered methods often fail to develop these competencies effectively. To address this issue, we developed a Project-Based Learning Model integrated with local wisdom (PBLM-e) within the Merdeka Belajar framework. The PBLM-e model enhances critical thinking and problem-solving skills by embedding culturally relevant, real-world problems into the learning process. This study employed a mixed-method approach, combining Research & Development (R&D) and experimental design, with 116 junior high school students in Makassar, Indonesia. Pre- and post-tests assessed students’ problem-solving abilities across four key indicators: understanding the problem, devising a plan, executing the plan, and reflecting on the solution. Results showed significant improvements in all indicators, demonstrating the model’s effectiveness in fostering essential skills. The integration of local wisdom made learning more meaningful, connecting academic content with students’ cultural contexts. The PBLM-e model presents a practical approach to preparing students for the challenges of Society 5.0, and future research should explore its long-term impact and the potential for incorporating advanced technologies.